Faktor-faktor yang Mempengaruhi Keputusan Wisatawan Backpacker Menginap di Kecamatan Kuta - Eki Sanjaya Ginting; Agung Sri Sulistyawati; Ni Made Ariani (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2019)
The trend of backpacking tourism is continuously developing and becomes one of the main factors of the rapidly growing low-budget accommodations as it happens in Bali especially at Kuta. Therefore, this study was aimed to define factors that affect backpackers to choose accommodations at Kuta District, so the stakeholders will at least have a reference to understand their potential guests especially those who aim backpackers as their main market. The sampling method of this study was area sampling. Data were collected by questionnaires, then were analyzed with factor analysis. The result showed that there were 5 main factors that affect backpackers to choose accommodations at Kuta District. They are special product factor, recommendation factor, reputation of the hotel, strategic location, and curiosity. These 5 factors were able to explain 64,775 percents of total variance and were considered capable of representing all variables that were included in each factor. The most dominant factor itself has taken by special product factor with eigen value 4,500 and 30,003 percents of variance. Suggestion for the stakeholders based on this study are to keep maintaining the cleanliness of the hotel and the comfort of the guest despite of the low price term. And for the governments were to maintain the traffic situation, providing public transportations, and to build awareness upon environment issues.